The role of procurement and freight forwarding in dealing with on-site scheduling problems - Salétli, Ákos; Cservenák, Ákos (Advanced Logistic Systems - Theory and Practice, 2023)
The problem of poor delivery schedules is one of the logistical problems that much more companies face than we should think at the first glance. But many companies may not realize this without the use of lean tools. This paper describes the role of procurement and supply management in dealing with a site scheduling problem, covering the concepts, history, responsibilities, sub-roles, and types.